Aligned poly (glycolide‐lactide) fiber membranes with conducting polypyrrole. (20th September 2016) - Guo, Huiling; Qiao, Tiankui; Jiang, Suchen; Li, Tongguo; Song, Ping; Zhang, Baochang; Song, Xiaofeng
Abstract : Electroactive polypyrrole (PPy) are highly attractive for a number of biomedical applications such as tissue engineering. To improve interfacial compatibility of PPy with biopolyesters, poly ( ɛ ‐caprolactone) grafted PPy (PPy‐ g ‐PCL) are synthesized in this work and characterized with Fourier transform infrared and nuclear magnetic resonance. PPy‐ g ‐PCL exhibits good conductivity and electrochemical activity. It is also blended with poly (glycolide‐lactide) to make aligned fiber membranes via drum at the speed of 1500 r/min. The relationships of blending ratio with the fibrous structure, thermal stability, wettability, and mechanical properties are clarified. The results show that blending PPy‐ g ‐PCL has no significant effect on the fibrous morphology, but fibers trends aligned architecture as the blend ratio of poly (glycolide‐lactide)/PPy‐ g ‐PCL exceeds 70/30. The membranous thermal and mechanical stability are modified. The membranous hydrophilicity significantly enhances with PPy‐ g ‐PCL amount increasing. Then the fiber membrane with topographical and electrical cues is qualified as the application of tissue engineering. Copyright © 2016 John Wiley & Sons, Ltd.